Analisis Panjang Bobot dan Faktor Kondisi Ikan Lidah (Cynoglossus lingua) di Sungai Berombang Kabupaten Labuhanbatu - Dewi Suci Lestari; Rusdi Machrizal (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Tongue Fish (C. lingua) is a fish that has a flat body like a tongue, has a non-bilateral symmetrical body, a blunt head, and belongs to the family Cynoglossidae. Tongue fish (C. lingua) usually lives on the bottom of muddy waters or mud mixed with sand and in river estuaries. The purpose of this study was to obtain related information about the analysis of the length and weight of the Tongue Fish (C. lingua) in the Berombang River, Panai Hilir District, Labuhanbatu Regency. This research lasted for 3 months, starting from October-December 2021. The sampling location was based on information from local fishermen. Fish samples were taken using nets, starting at 08.00 WIB - 16.00 WIB. The analysis carried out is the biological aspect of the relationship between length and weight of fish using a linear allometric model (LAM), while the ecological aspect that is measured is the condition factor using the K Fulton equation and the relative weight equation (Wr). In this study, 60 samples of Tongue Fish (C. lingua) were caught, with different lengths and weights. Where the total length ranges from 195-370 mm, with the total length of the dominant tongue fish on average 250 mm. While the weight of the Tongue Fish (C. lingua) ranged from 30-213 grams, and had an average dominant weight of 87 grams. The results of the long-weight relationship explained that the growth of the Tongue Fish (C. lingua) was positive allometric with the b value obtained, namely b > = 3, which was 3.3226.